Unmasking Job Satisfaction: Insights from Tribal India’s Nurses amongst the COVID-19 Pandemic - Vikrant Kabirpanthi; Vikas Gupta; Subramani Palaniyandi (Journal of Medical Evidence)
Background: Even prior to the pandemic, India’s nursing workforce faced a severe shortage, exacerbating the challenges they now face during the global health crisis. When compared to the WHO norm of 1:300, the lack of trained nurses is much worse, with a nurse-to-population ratio of 1:670. The level of job fulfilment experienced by healthcare workers on the frontlines is closely linked to how well strategies for preventing and managing significant emergencies are put into action and their overall impact. Aims: However, the job satisfaction status of Indian frontline healthcare staff during the fight against COVID-19 remains unexplored, so the present study was conducted to assess the job satisfaction during the pandemic of COVID-19 among the nurses. Patients and Methods: This cross-sectional, quantitative study was conducted for a duration of 1 month among 139 nursing staff currently working at hospital. A survey questionnaire was designed according to relevant guides, which gathered demographic details and job satisfaction using Job Satisfaction Scale (JSS) developed by Spector et al. The nurses were approached individually by investigator and were requested to complete the questionnaire on the same day. The MS Excel spreadsheet was used to enter the collected data. The Chi-square test was performed to find the association between poor JSS score and independent variables. An association was considered significant if the P < 0.05 for all tests (two-tailed) at a 5% level of significance. Results: The mean age for the 139 nursing staff was 27.37 ± 4.193 years. The overall mean score for JSS was 150.75 ± 31.591 and based on median (156 or less) as cut off for the poor JSS, nearly 47.5% of nurses were having poor JSS score. The Chi-square test analysis showed that the nurses of younger age (<25 years), staying at rented house, residing alone, working for more hours daily (6 or more) and having lesser night duties/month (<10 days) were significantly (P < 0.05) associated with the poor overall JSS. Conclusion: The findings of the study might be of great reference value for improving the job satisfaction level of nursing staff during public health emergencies, developing nursing staff security policies, and promoting the establishment of emergency response teams.